2018
DOI: 10.21315/mjps2018.16.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of the Role of Pharmacists and Willingness to Pay for Pharmacist-provided Dispensing Services: A Cross-sectional Pilot Study in the State of Sabah, Malaysia

Abstract: Pharmacists play an important role in healthcare delivery. Over the years, their role has shifted from product-oriented to patient-oriented. This study aimed to assess the perceptions of the public towards the role of pharmacists and the willingness of the public to pay for pharmacist-provided dispensing services in Sabah. This was a questionnairebased, cross-sectional study conducted from September 2014 to June 2015 in three major cities in Sabah, namely, Kota Kinabalu, Sandakan and Tawau. The respondents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…On the one hand, it might be related to the fact that the majority of Greek respondents were in their first- or second-year of studies and thus, they were not aware of the impact of drug management on patient’s overall management. According to Yau and Haque [ 30 ], it was indicated that the knowledge of PGx among students varied depending on the course of study and age, while Malay students had the same results in relevant questions, a fact that underlies the reliability and reproducibility of our observations [ 31 ]. On the other hand, it could be a result of cultural difference since pharmacists in Malaysia have a broader participation in the complete control of medication supply in comparison with their colleagues in Greece [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, it might be related to the fact that the majority of Greek respondents were in their first- or second-year of studies and thus, they were not aware of the impact of drug management on patient’s overall management. According to Yau and Haque [ 30 ], it was indicated that the knowledge of PGx among students varied depending on the course of study and age, while Malay students had the same results in relevant questions, a fact that underlies the reliability and reproducibility of our observations [ 31 ]. On the other hand, it could be a result of cultural difference since pharmacists in Malaysia have a broader participation in the complete control of medication supply in comparison with their colleagues in Greece [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Yau and Haque [ 30 ], it was indicated that the knowledge of PGx among students varied depending on the course of study and age, while Malay students had the same results in relevant questions, a fact that underlies the reliability and reproducibility of our observations [ 31 ]. On the other hand, it could be a result of cultural difference since pharmacists in Malaysia have a broader participation in the complete control of medication supply in comparison with their colleagues in Greece [ 31 ]. Indeed, Malay pharmacists have the authority to do medication reviews, identify medication issues and provide recommendations for better drug administration to patients and doctors.…”
Section: Discussionmentioning
confidence: 99%
“…The role of pharmacists in promoting public health has been investigated by some Malaysian researchers, with a focus on the attitude of community pharmacists in Penang state (7) and else, a knowledge, attitude and practice (KAP) study from the same state among the Penang's General Hospital pharmacists (8) . The respondents of another survey in Sabah state were consumers of pharmacy services, who responded the questions about pharmacy dispensing service charges (9) . Lack of publications on the attitudes of community pharmacists about their professional practice in Kuala Lumpur, as the capital city of Malaysia, prompted us to investigate this matter.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents were also found to be more likely to comply with a doctor's choice of medicine, regardless of price, and less likely to negotiate on the medicine price or ask for a discount. This could be because consumers are more concerned about receiving effective treatment regardless of cost, as reported in previous studies (30,34), or because they really trust their healthcare providers (35). The study by Schafheutle et al in England reported that a majority of their patients rarely and reluctantly discussed medicine prices and their affordability with their general practitioners (30).…”
Section: Discussionmentioning
confidence: 89%